Troto and the trucks - Shulevitz, Uri, 1935- (Margaret Ferguson Books, Farrar, Straus and Giroux, 2015)
Troto is a happy little car who likes to go places until he drives all the way to Cactusville and meets some big trucks that tease him for being so small.